POTENSI ANTAGONIS BAKTERIA SERRATIA MARCESSCENS TERHADAP BAKTERI STREPTOCOCCUS PYOGENESIS DAN BAKTERI VIBRIO CHOLERA SECARA IN VITRO - Muhammad Efendi; Dwi Wahyuni; Imam Mudakir (saintifika, 2016)
In indonesia, infection diseases are a very high problem among the public, one the common infectious diseases suffered by the Indonesian community is imflamtion of the tonsils caused by Streptococcus pyogenesis and Cholera caused by Vibrio cholera. The use of chemical antibiotics will have a negative impact in health, so necessary alternative replecement of natural antibiotics by Serratia mercescens can pruduce prodigiosin. This reseacrh was to test the potential of Serratia mercescens antagonist against Streptococcus phyogenesis and Vibrio cholera in vitro, using Completely Randomized Design with one treatment factor from Serratia mercescens bacteria concentration. The concentration used was 30μm for each bacterial suspension and added positive control in the form of chloramphenicol and negative control of aquades, each of which was repeated 3 repititions. The results were analyzed using one-way ANOVA and continued D- test. The result showed that Serratia mercescens had blocked inhibitability of Streptococcus phyogenesis bacteria with an average resistance of1.1033mm and on Vibrio cholera with an average resistance of 1.2233mm.